Perlindungan Hukum terhadap Pengguna Aplikasi E-Wallet DANA atas Kejahatan Phishing dan Hacking di Indonesia - Gemintang Septia; Lindawati; Rita Afria Ningsih; Shinta Dia Nurrul Faadhilah (Letterlijk, 2024)
The development of digital technology has led to an increasing use of digital wallets (e-wallets) as non-cash transaction instruments in society. One of the most widely used e-wallets in Indonesia is the DANA application. However, along with the growing use of e-wallets, various cybercrime risks such as phishing and hacking have also emerged, potentially causing losses to users. This study aims to analyze the forms of legal protection for users of the DANA e-wallet application against phishing and hacking crimes in digital services. The research employs a normative juridical method with a statutory and case study approach. The results indicate that although legal regulations concerning consumer protection and personal data security already exist, in practice DANA e-wallet users still experience difficulties in obtaining accountability for the losses they suffer. Legal protection for e-wallet users has not yet been implemented optimally; therefore, strengthening the role of service providers and enhancing law enforcement are necessary to ensure the security and protection of users’ rights.